The art of planning for library personnel. - Lorenzi, N M (1976)
A review of the planning process for personnel at the University of Cincinnati's new Health Sciences Library is discussed. The staff of two libraries were involved in the plan. The final organizational pattern encompassed present staff plus justification for additional staff who would be necessary in the expanded facility.